Ontological Thinking in Nizar Qabbani’s Poetry: The Poem “Book of Love” as a Model - sekkiou, sarah. (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract: The ideas of this research paper aim to clarify the ontological thinking of the poet of the feminine entity, Nizar Qabbani, who has always characterized his poetic orientation and poetic towards women and made them play a starring role in most of his creative books. And a man who loves women in general, as through the poem "The Book of Love" we will try to show the position of his wife in his existence as a whole, who, as much as he was courting her poetically, he was missing her personally and existentially.